Color Stability and Surface Properties of PMMA/ZrO2 Nanocomposite Denture Base Material after Using Denture Cleanser. (8th April 2021) - Gad, Mohammed M.; Abualsaud, Reem; Fouda, Shaimaa M.; Rahoma, Ahmed; Al-Thobity, Ahmad M.; Khan, Soban Q.; Akhtar, Sultan; Al-Abidi, Khalid S.; Ali, Mohamed S.; Al-Harbi, Fahad A.
Abstract : Statement of Problem. Novel polymethyl methacrylate (PMMA) containing zirconium dioxide nanoparticles (nano-ZrO2 ) was suggested as a denture base material but there is a lack of information regarding denture cleanser effects. Objectives . This study aimed to evaluate denture cleanser effects on color stability, surface roughness, and hardness of PMMA denture base resin reinforced with nano-ZrO2 . Materials and Methods . A total of 420 specimens were fabricated of unreinforced and nano-ZrO2 reinforced acrylic resin at 2.5% and 5%, resulting in 3 main groups. These groups were further subdivided ( n = 10) according to immersion solution (distilled water, Corega, sodium hypochlorite, and Renew) and immersion duration. Surface roughness, hardness, and color were measured at baseline (2 days- T 0 ) in distilled water and then after 180 and 365 days of immersion ( T 1 & T 2 ) in water or denture cleansing solutions. Data was collected and analyzed using two-way ANOVA followed by Bonferroni post hoc test ( α = 0.05). Results . Surface roughness increased significantly after denture cleanser immersion of unmodified and nano-ZrO2 -modified PMMA materials while hardness decreased (P < 0.001 ). The denture cleansers significantly affected the color of both PMMA denture bases (P < 0.001 ). The immersion time in denture cleansers significantly affected all tested properties (P < 0.001 ). Within denture cleansers, NaOCl showed the highest adverse effects (P < 0.05 ) while Renew showed the least adverse effects. Conclusion . Denture cleansers can significantly result in color change and alter the surface roughness and hardness of denture base resin even with ZrO2 nanoparticles addition. Therefore, they should be carefully used.